Noni Plant (Morinda Citrifolia L.) Growth and Development Influenced by Ambient Temperature and Humidity under Sub-tropical Conditions of Varanasi (India) - Singh, R. S.; Singh, D. R. (Indian Forester, 2012)
High valued medicinal plant of Noni (Morinda citrifolia L) were grown in Varanasi (25°18 N 83°01 E) during 2007-09 to assess the agro-climatic potential on the crop cultivation in sub-tropical and dry sub-humid conditions. The germination and emergence of noni seeds at an ambient temperature ranged between 23 and 36°C of September conditions has been studied. Highly significant linear relationships between the leaf tip appearance number (Y) and the heat units (X) was developed: Y = 0.0038X + 0.4823 with cc = 0.998 (significant at 1% level) for the seedling stage of the crop after the emergence. This indicated that the seedlings took about 254°C of growing degree days (GDD) for producing each new leaf tip before its transplantation. The, agro-meteorological measurements visualised that the noni seedlings growth ceased when ambient temperature was either < 12°C or > 40°C under Varanasi conditions. Study also indicated that the leaf tip production was the fastest (156°C leaf) on the plant under partial shading treatment (T2) followed by zero shading (T1) treatment (177°Cd leaf-1) and partial shading with compact soil (T3) treatment (201°Cd leaf-1) plants, after the transplantation. Height of the main shoot (MS) of the plants has increased rapidly and measured to highest (4.25m) again under T2 treatment followed by 3.0m under T1 treatment and lowest (2.95m) under T3 treatment at the end of second season (November 2009). Growing period for the noni crop was found nine months (270 days) from March to November. The plant took about 75 to 90 days time and at least 1250 to 1600°C of GDD for proper fruit development and to reach at semi ripening stage in Varanasi area.